(untitled) (Applied Biological Research, 2010)
Apple orchards in nine locations of Kashmir valley were surveyed in 2006 and 2007 for white rot and stem canker bark disease. Maximum disease incidence was noticed on scaffold branches and trunks of the trees. The anamorph of causal pathogen of white rot and stem canker was identified as Fusicoccum aesculi Corda, while the teleomorph as Botryosphaeria dothidea (Mung.Fr.) Ces. & De Not. Botryosphaeria dothidea is reported for the first time from the Jammu and Kashmir State.